Video Promotion Prehistoric Sites Archaeology Museum Sangiran - Harisna Wahyudihati; Twin Agus Pramonojati (KK Komunikasi Visual & Multimedia Fakultas Seni Rupa dan Desain Institut Teknologi Bandung, 2014)
This design aims to promote the World Prehistoric Archaeological Museum Sangiran to Indonesian and foreign people through audio-visual media is videography, contains information about Sangiran as National Heritage and included in the World Heritage Site which has been initiated by UNESCO. Besides, as an instrument for the Preservation Hall Ancient Man Sangiran site that can be used directly for educational purposes. Object of this study is the people of Indonesia and Abroad. Methods of data collection are done through literature review, observation, interviews, and questionnaires. Based on the research results, there are still many Indonesian people who do not know about the existence of Sangiran, even people who come from Central Java. This is of course influenced by several factors, one of which is the absence of instruments that functioned to promote to the public Sangiran with audio and visual media.With creative design and innovative video in terms of the concept and the content of a video that is an embodiment of the instrument can be a multimedia audiovisual media campaign appealing to the public.